Contribution of the Peruvian Society of Obstetrics and Gynecology to the specialty during 70 years from its creation, valued through the pages of The Peruvian Journal of Gynecology and Obstetrics - Pacheco-Romero, José (2017)
The Peruvian Society of Obstetrics and Gynecology (SPOG) was founded 70 years ago, in 1947, with the mission of contributing to the scientific progress in benefit of the Peruvian women. In 1955, the first number of The Peruvian Journal of Gynecology and Obstetrics (RPGO), the official journal of SPOG, was published with the name Ginecología y Obstetricia [Ginecol Obstet, o Ginecol Obstet (Perú)] until 2006, when the name changed to Revista Peruana de Ginecología y Obstetricia (Rev Peru Ginecol Obstet). An account of the Society’s activities may be retrieved through the editorials and papers written from the beginning of RPGO, as we observe the desire of the SPOG directors to have an organ of scientific communication where the leading obstetricians and gynecologists would publish their medical experiences and outcomes, as a source of information for the younger physicians. Research has contributed to the advancement in reproductive medicine, early diagnosis of gynecologic cancer, adequate delivery care, decrease in maternal and perinatal mortality, obstetrical hemorrhage, preeclampsia, pregnancy and newborn at high altitude, contraception, menopause, genital prolapse and urinary stress incontinence, breast pathology, genetics, ultrasound, endoscopic surgery, and many related themes. Members of SPOG have created institutional chapters such as the Fertility, Perinatology, Climacteric and Menopause, Ultrasound, Laparoscopic Surgery, Contraception, Fetal Medicine and others. The various SPOG Executive Committees have supported the RPGO permanence, and six Presidents of the Society took the challenge of managing the Journal in order to endorse its quality, punctuality and visibility. All the articles published since 1955 can be currently visited in its OJS web, where pdf files may be downloaded. Articles are also published in English. The RPGO is an open access journal and is indexed in important databases. There you can read about the burgeoning medical actions of the SPOG.